Korelasi Disiplin Sholat Lima Waktu dengan Kedisiplinan Mahasiswa Program Studi Kedokteran Program Sarjana Universitas Lambung Mangkurat - Aulia Rahmah, Rifka; Clarizza Dhea Nafadhika, Andi; Yasmin Raodhatul Isra, Putri; Muhammad Irhamna Husin, Gt (Pusat Pelatihan, Riset, dan Pembelajaran Bahasa, 2023)
This article aims to describe the correlation between prayer time discipline and the discipline of students in the Medical Study Program at Lambung Mangkurat University in 2022. The research method used is quantitative correlational analysis. In analyzing the correlation between the independent variable of five-time prayer discipline and the dependent variable of student discipline in the Medical Study Program at ULM in 2022, the researcher used partial correlation analysis and obtained a result of 0.13, indicating a strong relationship between the two variables. Based on the normality test using the Kolmogorov-Smirnov test, if the value is above 0.05, the data distribution is considered to meet normality. Therefore, it can be stated that H0 is rejected because H0: ρy1 = 0, and H1 is accepted because H1: ρy1 > 0. This means that there is a significant correlation between the discipline of performing the five-time prayer and the discipline of students in the Medical Study Program at ULM in 2022. Thus, it can be concluded that there is a significant correlation between the discipline of performing the five-time prayer and the discipline of students in the Medical Study Program at ULM in 2022.